DETERMINANTS OF MOMENTUM STRATEGY AND RETURN IN SHORT TIME HORIZON: CASE IN INDONESIAN STOCK MARKET - ADRIANUS (NIM 29014033), RIO
he profitability of momentum strategy remains a heavily discussed topic. Two main topics in this area that put great interest in researchers are the momentum profitability over various time horizon and its sources. This research examined both topics in Indonesian stock market for 685 trading days. In the subject of time horizon, it is shown that momentum strategy could be implemented profitably in 60, but not on 20 and 10 days. The results show that the profitability of momentum return was inversely related to its holding period. Average return for 60 days strategy was significantly higher than buy-and-hold by 3.30% on average while return for 10 days strategy was significantly lower from buy-and-hold by 1.68%. In the section of momentum return sources, it is found that sector rotation is significant in explaining momentum returns in both winner and loser portfolio for all of time horizon although has different explanatory power, while other variables have mixed influences. To conclude, momentum strategy could be profitable in Indonesia stock market in intermediate holding period and sector rotation has a significant role in explaining momentum returns.